PERANAN UNIVERSITAS ISLAM NEGERI SULTAN SYARIF KASIM RIAU DALAM KONSERVASI NASKAH KUNO MELAYU DI RIAU DALAM PERSPEKTIF UU. NO. 43 TAHUN 2007 - Elya Roza (Sosial Budaya, 2016)
Riau Malay manuscripts in the exact amount is not known except those stored in the museum, while the Malay manuscripts that saved by the people of Riau is predicted so much, it's just not known. It is important to note that in the Riau Malay manuscripts remain the property of the people of Riau. Lately, hunters Malay manuscripts from the neighboring country has managed to conserve the Malay manuscripts to be used in their collections. This situation needs attention because the manuscript was prone to lost or changed hands to outside parties. Actually, several agencies have been doing conservation in Riau Malay manuscripts by doing convention script, but convention that has been done was not received from the community owner or depositary because the rewards are not in accordance. This activity should be a concern of Local Government that aims to make Riau as a center of Malay culture. UIN Suska Riau as a partner in the field of education is responsible for human resources of the various aspects of science. Thus the Law no.43 of 2007 the law on Scripts should be understood and applied through study centers so socialized. Thus UIN Suska Riau can be a mediator even became a facilitator in manuscript conservation in Riau. In connection with this, then this paper attempts to examine the extent of UIN Suska Riau role in implementing the mandate contained in the legislation.